Projective Stochastic Equations and Nonlinear Long Memory. (December 2014) - Grublytė, Ieva; Surgailis, Donatas
Abstract : A projective moving average X t, t ∈ ℤ is a Bernoulli shift written as a backward martingale transform of the innovation sequence. We introduce a new class of nonlinear stochastic equations for projective moving averages, termed projective equations, involving a (nonlinear) kernel Q and a linear combination of projections of X t on 'intermediate' lagged innovation subspaces with given coefficients α i and β i, j . The class of such equations includes usual moving average processes and the Volterra series of the LARCH model. Solvability of projective equations is obtained using a recursive equality for projections of the solution X t . We show that, under certain conditions on Q, α i, and β i, j, this solution exhibits covariance and distributional long memory, with fractional Brownian motion as the limit of the corresponding partial sums process.